Soil erosion rate estimate using USLE of corn producing areas in Barangay Vitali, Zambonga City, Philippines - Garan, M. A.; Salang, E. D.; Galo, E. V.; Tabal, E. P. (International Journal of Agricultural Technology, 2021)
The rate of soil erosion using the universal soil loss equation (USLE) in seven (7) corn producing areas in Barangay Vitali, Zamboanga City, Philippines was estimated. The area is characterized as hilly with slope ranged from 20-43% and patches of banana, coconut and fruit trees where soil erosion has been a persistent problem. The corn areas and number of respondents were determined using the purposive sampling and descriptive statistics to compare the predictive variables. The USLE was used to estimate the rate of soil loss (A) measured in ton ha-1 yr-1 (t ha-1 yr-1) by the compounding effects of various factors such as the rainfall erosivity (R), soil erodibility (K), length of slope (L), steepness of slope (S), vegetation cover (C), farming practices and management (P). Accounting all these factors, of the 7 areas, Sitio Sta. Fe obtained the highest erosion rate measured at 214.86 t ha-1yr-1 followed by Sitios Pico, Camalig, Gemelina, Linduman, Tagpangi and Cansilayan with respective rate at 176.0, 111.51, 92.04, 88.05, 86.20 and 67.0 t ha-1yr-1, which gave the average of 119.62 t ha-1yr-1. Rainfall erosivity, length and slope gradient are factors which contributed to high erosion rates. Suitable, ecologically sound, climate smart-soil restorative technologies should replace the soil-erosive-monoculture corn farming in the uplands of Barangay Vitali. Substantial effort has to be in placed with strong interventions from government and local communities to help curb the increasing soil erosion problem in these fragile upland ecosystems in Zamboanga City, Philippines